Multivariable Discriminant Analysis for the Differential Diagnosis of Microcytic Anemia. (4th September 2013) - Urrechaga, Eloísa; Aguirre, Urko; Izquierdo, Silvia
Abstract : Introduction . Iron deficiency anemia and thalassemia are the most common causes of microcytic anemia. Powerful statistical computer programming enables sensitive discriminant analyses to aid in the diagnosis. We aimed at investigating the performance of the multiple discriminant analysis (MDA) to the differential diagnosis of microcytic anemia. Methods . The training group was composed of 200 β -thalassemia carriers, 65 α -thalassemia carriers, 170 iron deficiency anemia (IDA), and 45 mixed cases of thalassemia and acute phase response or iron deficiency. A set of potential predictor parameters that could detect differences among groups were selected: Red Blood Cells (RBC), hemoglobin (Hb), mean cell volume (MCV), mean cell hemoglobin (MCH), and RBC distribution width (RDW). The functions obtained with MDA analysis were applied to a set of 628 consecutive patients with microcytic anemia. Results . For classifying patients into two groups (genetic anemia and acquired anemia), only one function was needed; 87.9% β -thalassemia carriers, and 83.3% α -thalassemia carriers, and 72.1% in the mixed group were correctly classified. Conclusion . Linear discriminant functions based on hemogram data can aid in differentiating between IDA and thalassemia, so samples can be efficiently selected for further analysis to confirm the presence of genetic anemia.